Ekonomiczne uwarunkowania efektywności edukacyjnej uczniów - Jeżowski, Antoni (Economic Conditions of the Educational Effectivity, 2007)
The analysis of Polish students' performance in schools between 2000 and 2003 showed that social and economic factors are not being taken into consideration while creating education policy. Whom should results of this analysis interest? Whom should they above all serve for? These are difficult questions. One should take fast action to improve the situation in the education sector. Serious circles of experts and specialists should deal with it. Creating the political plan and the straight, opened and transparent law is the sine qua non of their action. Conclusions of these works should include taking into account different needs of individual pupils, groups, classes and schools in order to find for them the optimal number of teaching hours of reading, writing, understanding, editing, counting, the scientific thinking etc. Furthermore, the needs of education system should be identified followed by adapting to them local grant system, considering of private, national and union scholarships. Creating short- and long-term concepts concerning directions for teaching and learning as well as for preparing students for certain professions should reflect the demands of the job market. This all should be considered by teachers who will then find the best programme for their pupils. The most important thing is effective use of public means.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 730-739